Restaurant outlet density and the healthfulness of food purchases: evidence from FoodAPS - Volpe, Richard; Cai, Xiaowei; Tseng, Marilyn; Sinclair, Wilson (Frontiers in Nutrition, 2024)
Introduction The average American household’s diet and food purchasing patterns are out of sync with federal recommendations. Researchers have connected this with the large and growing rates of obesity, diabetes, and other diet-related ailments in the U.S. Restaurant food has been discussed a potential contributor to unhealthful diets, as it is often calorically dense. We investigate the association between household access to restaurants and diet quality using USDA FoodAPS data and NPD ReCount data. Methods We define radii around households to measure restaurant outlet counts and apply a regression analysis incorporating household characteristics. Results We find that neither restaurant counts nor openings share many statistically or economically significant associations with average dietary quality. Household characteristics and demographics are far more powerful in explaining variation in diet quality. Discussion Our findings align with the large and growing body of empirical research that suggests that personal preferences and other household characteristics are more important than the food environment in explaining food choices and diet quality. Given the extant research on the importance of access to large supermarkets, our results suggest that access to food retailers is more important in explaining diet quality than access to restaurants.